Life cycle assessment of the hydrothermal carbonization process applied to the wet fraction mechanically separated from municipal mixed waste - Lombardi, Lidia (Waste management (New York, N.Y.), 2023)
Copyright © 2023 Elsevier Ltd. All rights reserved.